2020
DOI: 10.1097/md.0000000000022128
|View full text |Cite
|
Sign up to set email alerts
|

First-line pemetrexed and carboplatin plus anlotinib for epidermal growth factor receptor wild-type and anaplastic lymphoma kinase-negative lung adenocarcinoma with brain metastasis

Abstract: Rationale: Brain metastasis (BM) is a serious complication in non-small cell lung cancer (NSCLC) patients. Pemetrexed is one of the preferred agents in nonsquamous NSCLC with BM; however, the traditional chemotherapy demonstrated limited efficacy partly due to drug resistance and the blood-brain barrier. Patient concerns: A 52-year-old male non-smoker was admitted for irritating cough, chest distress, and back pain. Diagnoses: Epidermal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“… 33 A case reported that first-line pemetrexed and carboplatin plus anlotinib achieved CR for the treatment of EGFR wild-type NSCLC. 22 In our study, anlotinib plus chemotherapy had a tendency to prolong survival and had a significantly longer mPFS in patients <=65 years and first-line treatment than anlotinib monotherapy group. These studies suggest that anlotinib combined with chemotherapy may be an effective treatment for advanced NSCLC.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“… 33 A case reported that first-line pemetrexed and carboplatin plus anlotinib achieved CR for the treatment of EGFR wild-type NSCLC. 22 In our study, anlotinib plus chemotherapy had a tendency to prolong survival and had a significantly longer mPFS in patients <=65 years and first-line treatment than anlotinib monotherapy group. These studies suggest that anlotinib combined with chemotherapy may be an effective treatment for advanced NSCLC.…”
Section: Discussionsupporting
confidence: 43%
“…[11][12][13][14][15][16][17] Current studies have shown encouraging efficacy of the clinical use of anlotinib combination therapy, and a case reported first-line pemetrexed and carboplatin plus anlotinib achieved CR. [18][19][20][21][22] However, the sample size of current studies is small and more studies are still needed to confirm the efficacy and safety of anlotinib combination therapy in different patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the combination therapy of chemotherapy and anlotinib is effective and widely used in clinical practice. Zhang C. et al (2020) reported the case of a patient with lung adenocarcinoma with brain metastasis treated with chemotherapy drugs plus anlotinib who achieved PFS of more than 2 years. Wang et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“… 9 Several studies identified the feasibility of anlotinib plus chemotherapy in the treatment of advanced NSCLC. 10 , 11 The combination of antiangiogenic agent and chemotherapy may be a novel development direction for T790M‐negative EGFR ‐mutant advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Anlotinib reversed acquired resistance to EGFR TKIs via fibroblast growth factor receptor 1 (FGFR1) signaling pathway in T790M‐negative EGFR ‐mutant NSCLC in an in vitro trial 9 . Several studies identified the feasibility of anlotinib plus chemotherapy in the treatment of advanced NSCLC 10,11 . The combination of antiangiogenic agent and chemotherapy may be a novel development direction for T790M‐negative EGFR ‐mutant advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%